General Solution and Observability of Singular Differential Systems with Delay - Jiang Wei (Abstract and Applied Analysis)
We study singular differential systems with delay. A general description for the solutions of singular differential systems with delay is given and a necessary and sufficient condition for exact observability of singular differential systems with delay is derived.